Parents' Efforts in Instilling Religious Attitudes for Early Childhood through a Religious Psychology Approach in Kp. Bojong - Ghina Agniya Suhulah; Nadya Yulianty (AMIN: International Journal of Islamic Education and Knowledge Integration, 2023)
Children at an early age are a very valuable part, therefore it is termed the golden age, this period will not be repeated a second time. This paper discusses how the internalization of religious attitudes that we must give since early childhood (age 0-6 years). Because at this age, we can instill the values of faith (tawhid), the value of worship and also moral values.  These values if internalized at an early age, it will be a provision for the growth and development of children later. Because these values can form a religious attitude in accordance with the basic values of Islam. Islamic education is able to give birth to a religious attitude in children from an early age, if internalized on an ongoing basis.   Because Islamic education is an educational system that demands to train students to have values and personalities in accordance with religious demands.